The impact of AGN feedback on galaxy intrinsic alignments in the Horizon simulations. Issue 3 (17th January 2020) - Soussana, Adam; Chisari, Nora Elisa; Codis, Sandrine; Beckmann, Ricarda S; Dubois, Yohan; Devriendt, Julien; Peirani, Sebastien; Laigle, Clotilde; Pichon, Christophe; Slyz, Adrianne
ABSTRACT: The intrinsic correlations of galaxy shapes and orientations across the large-scale structure of the Universe are a known contaminant to weak gravitational lensing. They are known to be dependent on galaxy properties, such as their mass and morphologies. The complex interplay between alignments and the physical processes that drive galaxy evolution remains vastly unexplored. We assess the sensitivity of intrinsic alignments (shapes and angular momenta) to active galactic nuclei (AGN) feedback by comparing galaxy alignment in twin runs of the cosmological hydrodynamical Horizon simulation, which do and do not include AGN feedback, respectively. We measure intrinsic alignments in three dimensions and in projection at $z$  = 0 and $z$  = 1. We find that the projected alignment signal of all galaxies with resolved shapes with respect to the density field in the simulation is robust to AGN feedback, thus giving similar predictions for contamination to weak lensing. The relative alignment of galaxy shapes around galaxy positions is however significantly impacted, especially when considering high-mass ellipsoids. Using a sample of galaxy 'twins' across simulations, we determine that AGN changes both the galaxy selection and their actual alignments. Finally, we measure the alignments of angular momenta of galaxies with their nearest filament. Overall, these are more significant in the presence of AGN as a result of the higher abundance of massive pressure-supported galaxies.